Verbal Humor: a Salient Case in Translation and Translatability - A. Effendi Kadarisman (Pascasarjana UM, 2017)
Abstract: This article aims to answer the following research question: are jokes and puns translatable? Using a linguistic approach and collecting relevant data (i.e., jokes and puns in Indonesian and English), this article tries to investigate their translatability. A thorough linguistic analysis shows that there are two kinds of verbal humor: logic-twisting humor and ambiguity-manipulating humor. Verbal humor of the first type is in general translatable; for the translation is an act of rendering meaning. Conversely, verbal humor of the second type is typically untranslatable; for the translation is an act of rendering double correspondence: both form and meaning. Key Words: humor translation, jokes and puns, (un)translatability, arbitrariness principleAbstrak: Artikel ini bertujuan menjawab pertanyaan penelitian: apakah lelucon dan permainan-kata dapat diterjemahkan? Dengan menggunakan ancangan linguistik dan mengumpulkan data yang relevan (berupa lelucon dan permainan-kata dalam bahasa Indonesia dan bahasa Inggris), tulisan ini mencoba menjajagi kadar keterjemahan humor. Hasil analisis linguistik menunjukkan bahwa humor ada dua jenis: permainan logika dan permainan ambiguitas. Humor jenis pertama gampang diterjemahkan, karena penerjemahannya merupakan upaya alih-makna. Sebaliknya, humor jenis kedua tak bisa diterjemahkan, karena upaya alih-bentuk-dan-makna sekaligus merupakan upaya yang mustahil.Kata kunci: terjemahan lelucon, lelucon dan permainan-kata, ketidakterjemahan, prinsip arbitrer